Perinatal risk factors for low and moderate five-minute Apgar scores at term. (March 2017) - Lai, Shimona; Flatley, Christopher; Kumar, Sailesh
Abstract: Objective: To evaluate the specific maternal and perinatal variables associated with a low (≤3) or moderate (4–6) Apgar score, compared to a high (≥7) score. Study design: This was a retrospective, cohort study of 58429 term singleton babies born at the Mater Mother's Hospital in Brisbane, Australia in 2007–2013. Maternal demographics, socio-economic status using the Australian Socioeconomic Index for Areas (SEIFA) score, obstetric factors, and birth outcomes were compared for neonates grouped into three categories based on their five-minute Apgar: low (≤3), moderate (4–6) and high (≥7). The low- and moderate-score cohorts were individually compared to the high-score cohort using both univariate and multivariate analysis. Results: Logistic regression analysis confirmed that of the variables analysed, only maternal public insurance status (OR 2.1, 95% CI 1.5–3.1), breech presentation (OR 2.4, 95% CI 1.1–4.6), other non-cephalic presentation (OR 9.5, 95% CI 2.2–25.4), intramuscular narcotic use (OR 2.3, 95% CI 1.5–3.5), and presence of meconium (OR 3.7, 95% CI 2.5–5.4) were significantly associated with low Apgar scores. Variables significantly associated with a moderate score were: SEIFA ≤50th centile (OR 1.6, 95% CI 1.2–2.0) and 61st to 70th centile (OR 1.31, 95% CI 0.9–1.8) categories, maternal public insurance status (OR 2.7, 95% CI 2.2–3.3), nulliparity (OR 2.0, 95% CI 1.7–2.5), emergency caesarean birth (OR 2.6, 95% CI 2.1–3.2), instrumental birth (OR 2.3, 95% CI 1.9–2.9), and presence of meconium (OR 2.6, 95% CI 2.1–3.2). Conclusions: Factors associated with low and moderate Apgar scores vary in type and degree of influence. Distinctions in the perinatal background can help predict newborn compromise and accelerate delivery of care.